2010 10th IEEE-RAS International Conference on Humanoid Robots 2010
DOI: 10.1109/ichr.2010.5686346
|View full text |Cite
|
Sign up to set email alerts
|

Collaborating with Kaspar: Using an autonomous humanoid robot to foster cooperative dyadic play among children with autism

Abstract: Abstract-This article describes a pilot study in which children with autism alternated between playing a cooperative, dyadic video game with an adult human and playing the same game with an autonomous humanoid robot. The purpose of the study was to determine whether the children, all of whom had difficulties communicating and engaging in social play with others, would display more collaborative behaviours when playing with an adult after playing and interacting with the humanoid robot. Based on our analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 24 publications
1
36
0
2
Order By: Relevance
“…Children with ASD show a great affinity for robots, computers, and mechanical components [3]. In the field of socially assistive robotics (SAR), robots are used as tools in socialization therapies for children with ASD in order to enhance social engagement, imitation, and joint attention skills [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Children with ASD show a great affinity for robots, computers, and mechanical components [3]. In the field of socially assistive robotics (SAR), robots are used as tools in socialization therapies for children with ASD in order to enhance social engagement, imitation, and joint attention skills [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, similarity between the two movements is enforced by the cost function of the proposed framework that maximizes similarity between human angle trajectories and robot trajectories as described in (3) and (4). Thus, the similarity between the angle trajectories of human and robot is examined in order to assess the similarity between the motions.…”
Section: ) Similarity Between Human Motion and Robot Motionmentioning
confidence: 99%
“…UMANOID robots have been used in a wide range of applications that require human-robot interaction including entertainment [1,2,3], healthcare [4,5], and assistive living [6]. They have also been used for assisting children with learning difficulties [7] to encourage social interaction [8,9] and provide verbal and/or physical encouragement [10].…”
Section: Introductionmentioning
confidence: 99%
“…The study done by Wainer and Dautenhahn reported in [101] describes an experiment in which six children with ASD played a dyadic video game alternatingly with an adult and KASPAR, in four 25-minute sessions over a period of three weeks. The two players had to stand on opposite sides of a single flatbed computer monitor, while taking turns and communicating with each other, either verbally or by pressing buttons, to decide which of the many shapes on the screen both of them would select.…”
Section: Turn Takingmentioning
confidence: 99%
“…happy, neutral, sad, and surprise), and gestures to interact with a human [97]. Case study evaluations suggest that KASPAR can encourage children to engage in social interactions with peers or adults [98][99][100][101].…”
Section: Robotic Interventionmentioning
confidence: 99%